Irrigation in Aija - Antúnez de Mayolo R., Santiago Erik (1986)
The secular process of aridization of our country advances from S to N and from O to E (Antúnez, 1976). The volume of rainfall from this cause decreases by approximately 7% per century. Added to this reduction of water in the rivers is the decrease caused by the melting of the mountain ranges, which, from 2,872m3/s of water that they provided in 1532, today only contribute about 350m3/s. The Incas were aware of this aridization process and controlled it by irrigating the high Andean pastures (Antúnez, 1981). From Pizarro, the Hispanic domination and during the Republican one, the aridization and desertification of the territory increased in increasing form.